The Effect of Tax Incentives, Quality of Human Resources, and Service Satisfaction on Taxpayer Compliance (Case Study on Individual Taxpayers in Madiun City) - Salman, Kautsar Riza (Library of Sultan Agung Islamic University, 2024)
There are various kinds of sectoral policies in each region to increase taxpayer compliance, including through the provision of incentives and improving the quality of service to taxpayers. This study aims to obtain empirical evidence regarding the effect of providing tax incentives, the quality of human resources and service satisfaction on taxpayer compliance. This research is a quantitative study with the object of research being individual taxpayers registered in the city of Madiun. The number of samples obtained was 120 respondents. The data used is included in the primary data by distributing questionnaires through the Google form. This study uses multiple linear regression analysis techniques with the SPSS 26 program. The results show that: (1) tax incentives have an effect on taxpayer compliance, (2) the quality of human resources has an effect on taxpayer compliance, and (3) tax service satisfaction has an effect on taxpayer compliance.